Pengaruh Kompensasi, Gaya Kepemimpinan, dan Motivasi Kerja Terhadap Kinerja Karyawan Generasi Z di Indonesia - Steven Keane; Alan Setiawan; Michael Abed Nego Harianja; Amal Vieri (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explain whether there is an influence of compensation (X1), leadership style (X2), and work motivation (X3) on employee performance (Y) in generation z in Indonesia. The population used in this study were young children of generation z who had entered the workforce. The sample was determined by the purposive sampling method with a total of 100 respondents. Data were collected through a questionnaire in the form of a google form that was distributed. The results of this study indicate that compensation has a negative and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count -2.491 <t table 1.660 and a significant level of 0.017 <0.05, leadership style has a positive and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count 13.811 <t table 1.660 and a significant level of 0.000 <0.05, work motivation has a positive and significant effect on the performance of generation z employees in Indonesia with a regression coefficient of t count 5.688 <t table 1.660 and a significant level of 0.000 <0.05, this shows that compensation has a negative and significant effect on the performance of generation z employees in Indonesia, leadership style and work motivation have a positive and significant effect on the performance of generation z employees in Indonesia.